Analisis Rasionalitas Penggunaan Obat Dispepsia Di Puskesmas Pamarayan - Candra Junaedi; Sumarlin Sumarlin; Agnes Safitri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Dyspepsia includes a collection of clinical symptoms consisting of discomfort or persistent (episodic) or recurrence in the upper abdomen. Dyspepsia can be influenced by several factors, including increased gastric acid secretion, diet, and environmental factors, as well as psychological factors such as stress. This research aims to determine the use of dyspepsia medication at the Puskesmas Pamarayan. The type of research used in this research is descriptive observational with a purposive sampling method. The population in this study was 230 dyspepsia patients who visited the Puskesmas Pamarayan. The sample in this study was 31 respondents who had been determined using the Slovin formula with an error tolerance limit of 5%. Data were analyzed descriptively using rationality guidelines which include correct diagnosis, correct drug selection, correct dose, correct time interval, alertness to side effects, and correct information. The results of the study showed that the treatment of dyspepsia at the Puskesmas Pamarayan was rational.